Antibiotic resistance and biofilm formation in children with Enteropathogenic Escherichia coli (EPEC) in Brazilian Amazon - Renata Santos Rodrigues; Nucia Cristiane da Silva Lima; Roger Lafontaine Mesquita Taborda; Rosimar Pires Esquerdo; Antonieta Rodrigues Gama; Paulo Afonso Nogueira; Patricia Puccinelli Orlandi; Najla Benevides Matos (Journal of Infection in Developing Countries)
Introduction: Enteropathogenic Escherichia coli is an important causative agent of diarrhea in both developed and developing countries.